Implementasi Etnopedagogi Pada Tradisi Adat Suku Sasak: Implementasi Etnopedagogi Pada Tradisi Adat Suku Sasak - Asri, Indra Himayatul; Lestarini, Yuniar; Muspita, Zalia; Sulastri, Andi; Kudsiah, Musabihatul; Fadilah, Dina; Rohini, Rohini (Educatio, 2024)
Indonesia has a colorful culture, thousands of tribes with their own characteristics, including the Sasak tribe on Lombok Island which has a very unique cultural style. Therefore, it is very possible to explore the educational values ​​contained in the traditions that are still carried out by the people of Lombok which are based on religious values ​​and norms (religion) and based on communal conventions (agreements) which are better known as the Sasak tribe community (Sasak custom). Sasak society is a social group in which spiritual and structural relationships occur which enable the formation of long-term agreements and shared beliefs which are called culture. The Sasak people are a society that still adheres to its culture to this day. Currently, the Sasak tribe is not only a community group but also an ethnic group that adds to the rich traditions of the Indonesian people. One of the Sasak tribal traditions whose educational value can be seen is the Bale (house) and the Nyongkolan tradition. Keywords: Sasak tribe, Bale, Nyongkolan